Perioperative Management of Interscalene Block in Patients with Lung Disease - Eric S. Schwenk; Kishor Gandhi; Eugene R. Viscusi (Case Reports in Anesthesiology)
Interscalene nerve block impairs ipsilateral lung function and is relatively contraindicated for patients with lung impairment. We present a case of an 89-year-old female smoker with prior left lung lower lobectomy and mild to moderate lung disease who presented for right shoulder arthroplasty and insisted on regional anesthesia. The patient received a multimodal perioperative regimen that consisted of a continuous interscalene block, acetaminophen, ketorolac, and opioids. Surgery proceeded uneventfully and postoperative analgesia was excellent. Pulmonary physiology and management of these patients will be discussed. A risk/benefit discussion should occur with patients having impaired lung function before performance of interscalene blocks. In this particular patient with mild to moderate disease, analgesia was well managed through a multimodal approach including a continuous interscalene block, and close monitoring of respiratory status took place throughout the perioperative period, leading to a successful outcome.